TINGKAT KEPUASAN NASABAH DIPENGARUHI OLEH ANALISIS TINGKAT KEPENTINGAN DAN KEPUASAN NASABAH - Basuki Basuki; Rahmi Widyanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
This research about are quite similar reasons for debtors in selecting bank to the reasons in keeping funds. It is not merely concerning interest rate and facility, service is also an important factor. This factor is greatly important regarding business activity between one bank and others can be said to be the same. The different thing is a matter of services.This research is located in Kalsel Syariah Bank Banjarmasin Branch. This research aims to (1) determine and analyze the level of conformity of interest level of service elements according to customers on the performance that has been conducted by Kalsel Syariah Bank Banjarmasin Branch (2) to determine customers’ satisfaction on the services that have been given so that it can assist the Kalsel Syariah Bank performance to achieve better quality improvement through determination of main priority.The samples are 100 customers of Kalsel Syariah Bank Banjarmasin Branch as the respondents using accidental sampling technique, the analysis used is customers’ Importance-Performance analysis. This analysis uses Cartesians Diagram divided into four quadrants. In this research, there are some main considerations by Kalsel Syariah Bank Banjarmasin Branch namely (a) Teller attention to the customers, employee willingness to service the customers (b) Waiting time in the queue (c) existence of Kalsel Syariah ATM machine (d) Interest rate level given by the bank.